Cloning, molecular analysis and transcriptional regulation of the Schizosaccharomyces pombe malic enzyme gene - Viljoen, Marinda,1968- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.